2004
DOI: 10.1002/cne.20145
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics of CNS‐associated neurohemal systems of adult Drosophila melanogaster: A mass spectrometric survey of peptides from individual flies

Abstract: Neuropeptides are important messenger molecules that influence nearly all physiological processes. In insects, they can be released as neuromodulators within the central nervous system (CNS) or as neurohormones into the hemolymph. We analyzed the peptidome of neurohormonal release sites and associated secretory peptidergic neurons of adult Drosophila melanogaster. MALDI-TOF mass spectrometric analyzes were performed on single organs or cell cluster from individual flies. This first peptidomic characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
184
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(207 citation statements)
references
References 45 publications
18
184
2
Order By: Relevance
“…In accordance with this finding, it has been shown that AKH peptides are present in the brain and in neuronal projections innervating the midgut in mosquitoes [24,28]. In several peptidomics studies on D. melanogaster, the signal of mature AKH was very weak [29,30], whereas intermediate AKH peptides were clearly detected [31]. The same was found in the Australian sheep blowfly Lucilia cuprina, and the anautogenous flesh fly Sarcophaga crassipalpis [25].…”
Section: Distribution Of Detected Neuropeptidessupporting
confidence: 60%
“…In accordance with this finding, it has been shown that AKH peptides are present in the brain and in neuronal projections innervating the midgut in mosquitoes [24,28]. In several peptidomics studies on D. melanogaster, the signal of mature AKH was very weak [29,30], whereas intermediate AKH peptides were clearly detected [31]. The same was found in the Australian sheep blowfly Lucilia cuprina, and the anautogenous flesh fly Sarcophaga crassipalpis [25].…”
Section: Distribution Of Detected Neuropeptidessupporting
confidence: 60%
“…Body sizes of the The Western blot analysis with phospho-ERK in Drosophila BG2-c6 cells shows that sNPF1 and sNPF2 peptide treatments increased the activation of ERK compared to those of the non-treated and the sNPF2 [1][2][3][4][5][6][7][8][9][10] peptide treated controls. However, sNPF3 and sNPF4 peptide treatments did not increase ERK activation.…”
Section: Measurement Of Body Size and Weightmentioning
confidence: 99%
“…2A). However, in previous mass spectrometry studies using larval and adult tissues, AQRSPSLRLRFa (sNPF1), SPSLRLRFa (sNPF2 [12][13][14][15][16][17][18][19] ), SDPDMLNSIVE (sNPF-AP-1), WFGDVNQKPI (sNPF2 [1][2][3][4][5][6][7][8][9][10] ), SPSLRLRFa (sNPF2 [12][13][14][15][16][17][18][19] ) peptides are found [7][8][9]. PQRLRWa (sNPF3) and PMRLRWa (sNPF4) are also identified in adult body extract [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, hugin-PK, but not hugin-gamma, was found in the corpora cardiaca/ring gland of D. melanogaster 14,15 and other Drosophila species. 16 What is the explanation for not finding hugin-gamma?…”
Section: Hugin and Pban Propeptide Processingmentioning
confidence: 91%
“…In this respect, hugin may be part of a neuronal circuit involved not only in making a decision between feeding and not feeding, but also in making perhaps an even tougher decision: between feeding and mating. Chemically identified peptides [14][15][16][26][27][28] are boxed in red, the PRXa C-termini are boxed in blue. Peptide designations (see Roman numbers) refer to common peptide designations from M. sexta, H. zea, and D. melanogaster.…”
Section: Functional Implicationsmentioning
confidence: 99%